2013
DOI: 10.5897/jmpr2013.5312
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic and genotoxic effects on Wistar rats treated with aqueous extract from Chrysobalanus icaco L.

Abstract: Chrysobalanus icaco L. is a medicinal plant, used to treat diabetes and dyslipidemia in Brazil. The biological effects may vary depending on the source of plant. Experiments were performed to assess these effects from plants collected in the field and those obtained from dried herbs market. Glycemia, cholesterol and triglycerides serum concentrations were measured in healthy and diabetic rats treated with aqueous extract of leaves. Diabetic rats treated with the extract showed lower serum triglycerides, but th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
2
0
3
Order By: Relevance
“…The extract did not affect food intake or weight gain; however, it decreased adipose tissue gain, triglyceride levels, and excretion of lipids in feces, in addition to increasing locomotor activity and normalizing sensitivity insulin and glucose tolerance (White et al, 2016a). Ferreira-Machado et al (2014), report that the administration for 35 days of 0.7 mg/mL of aqueous extracts of C. icaco leaves shows a significant reduction in triglyceride levels was observed in diabetic rats, the values being the same as those of the control group (80 mg/dL).…”
Section: Anti-diabetic Activity and Effects In Lipogenesis And Adipositymentioning
confidence: 98%
See 1 more Smart Citation
“…The extract did not affect food intake or weight gain; however, it decreased adipose tissue gain, triglyceride levels, and excretion of lipids in feces, in addition to increasing locomotor activity and normalizing sensitivity insulin and glucose tolerance (White et al, 2016a). Ferreira-Machado et al (2014), report that the administration for 35 days of 0.7 mg/mL of aqueous extracts of C. icaco leaves shows a significant reduction in triglyceride levels was observed in diabetic rats, the values being the same as those of the control group (80 mg/dL).…”
Section: Anti-diabetic Activity and Effects In Lipogenesis And Adipositymentioning
confidence: 98%
“…Although C. icaco is a source of other phytochemicals like terpenes, most often flavonoids like flavonols and anthocyanins are most studied in fruits. These molecules stand out for their hypoglycemic, antiobesogenic, hypolipidemic, and antioxidant activity, these in vitro and in vivo models, so could become a profitable and sustainable alternative, in the treatment of these conditions (White et al, 2016a;White et al, 2016b;Portela-de-Sá et al, 2020;Nayak et al, 2011;Ferreira-Machado et al, 2014;de Oliveira et al, 2013), in addition to the fact that no acute toxicity has been observed (Ribeiro et al, 2020).…”
mentioning
confidence: 99%
“… Foi avaliado in vivo, em experimento com ratos, que o extrato aquoso das folhas é potencialmente genotóxico. Ademais, avaliou-se que ratos diabéticos tratados com o extrato apresentaram redução nos níveis de triglicerídeo, sem diferenças significativas nos níveis de glicemia e colesterol 19 . 79,80 .…”
Section: Chrysobalanus Icacounclassified
“…A partir dos dados da Tabela 9, verifica-se que a relação para a regressão apresentou o valor de 0,2096, ficando muito abaixo da relação esperada. Adicionalmente, o valor de F calculado para a falta de ajuste do modelo (72,55) foi superior ao F tabelado (19,16), fornecendo uma alta relação, o que igualmente não é ideal para a validação do modelo, pois para que um modelo seja considerado bem ajustado essa relação deve ser inferior a 0,10 121 .…”
Section: Condições Ce-dadunclassified
See 1 more Smart Citation